Prescribing pattern of non-steroidal anti-inflammatory drugs at outpatient departments of teaching hospitals - Md. Shamsur Rahman; Zinnat Ara Begum; Md. Khoshroz Samad (Bangladesh Pharmacological Society, 2007)
The prescribing pattern of non-steroidal anti-inflammatory drugs (NSAIDs) in prescriptions prescribed by the qualified medical personnel in the outpatient departments of three selected teaching hospitals in Dhaka city were studied. A total of 600 prescriptions containing NSAIDs were collected. The clinical conditions for which NSAIDs prescribed were identical in all the three hospitals, although there were wide variations in the prescribing pattern with respect to pharmacological sub-classes of NSAIDs. Analgesics with no or minimal anti-inflammatory effects were the most commonly prescribed NSAIDs in the medical outpatient departments of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University Hospital (BSMMUH) whereas analgesics with potent anti-inflammatory effects were the most commonly prescribed NSAIDs in a private teaching hospital (PH). Moreover, the prescribers in PH had to prescribe additional drugs than those of the prescribers of DMCH and BSMMUH to counter the adverse effects of NSAIDs. Proton pump inhibitors were mainly used in medical outpatient departments whereas H2 blockers were in surgical outpatient departments. Consequently, the cost of prescribed NSAIDs per prescription and ultimately the cost of total drugs per prescription became more expensive in PH compared to DMCH and BSMMUH. In conclusion, it may be said that the overall prescribing pattern of NSAIDs among three hospitals is rational.